Multi-environment factors dominate plant community structure and diversity in an ombrotrophic bog: The water level is the main regulating mechanism - Li, Yue; Wang, Xue; He, Chunguang; Jiang, Haibo; Sheng, Lianxi (Frontiers in Environmental Science, 2022)
Understanding the relationship between vegetation and the environment is critical to manage bog ecosystems. However, information on how environmental factors influence the species composition and diversity in the ombrotrophic bog of Northeast China is lacking. Here, we investigated species compositions and environmental characteristics (water level, water conductivity, soil moisture content, bulk density, pH, organic carbon, total nitrogen, total phosphorous) from 5 sample sites along the water level gradients (the water level is below the surface, near the surface, and above the surface). Plant communities presented a patchy distribution pattern along the environmental gradients and could be divided into five types of communities. Moreover, the distribution of plant communities was mainly determined by water level, water conductivity, soil moisture content, pH, and organic carbon, which significantly explained 32.2%, 30.9%, 29.7%, 29.1%, 22.5% of the variation in floristic composition. Among these factors, water level was the dominant factor influencing the distribution of plant communities. The partial least squares path model analysis showed that water level could influence plant diversity through different pathways, which could directly affect plant diversity and indirectly affect by changing water chemistry and soil properties. Additionally, soil pH contributed most to the indirect effects of water level on plant diversity. Thus, this study highlighted the high dependence of plant communities on water level and environmental factors driven by water level in ombrotrophic bogs, which provided some valuable implications for regional vegetation restoration and plant community stability.